DIGITAL MARKETING AND PRODUCT BRANDING IN TOASTED BREAD MSMES PLAYERS - Bahar, Harmiaty (Laboratorium Riset Ekonomi, 2024)
In the growing digital era rapidly, many MSMEs, including toast MSMEs in Kendari City, are facing challenges in implementing effective digital marketing strategies to build and strengthen their product branding. This study aims to analyze implementation digital marketing in increasing brand awareness and sales toasted bread MSMEs products in Kendari City. The method used is qualitative research with interviews in-depth study of MSME actors and data analysis through a thematic approach. The results of the study show that although MSME actors have utilized digital platforms such as social media and marketplaces, the challenges The main problem faced is the lack of understanding of effective digital marketing strategies and their limitations resources. Digital marketing is proven increase visibility brand and sales product, but still need more structured management. The implications of this research provide insight practical for MSMEs to optimize digital marketing strategies and provide recommendations policies to support the development of technology- based MSMEs.